Segurança e defesa no Cone Sul: Transições com transformações? - Soares, Samuel Alves [UNESP] (Pontifícia Universidade Católica do Rio Grande do Sul (PUC-RS), 2008)
The new conditions of international security don't only attach importance to sovereignty and interstate relations. This new framework has led to changes in the scope and requirements for Politics of Defense. Countries of the Southern Cone seek to establish new parameters in the definition of their policies, but need to define between dissuasive policies, as in the past, or establish mechanisms for cooperation with their neighbors. Furthermore, these policies, by their nature and size, are not exclusively militaries. The purpose of this article is to examine the definitions constraints on strategic deterrence and cooperation in international security, and identify the degree of autonomy and the nature of the concepts derived from the armed forces in shaping Politics of Defense. Finally, we try to check the level of civil policy direction in defining those policies.
Security and defense in the Southern Cone: Transitions with transformations?
Keywords: Deterrence and cooperation; Politics of defense; Southern Cone